TREATMENT OF A LARGE LENTIGO MALIGNA AND LENTIGO MALIGNA MELANOMA WITHIN THE LESION WITH INCISIONAL BIOPSY AND 5% IMIQUIMOD - Gajić, Milica; Ogorelica , Dejan; Ivkov-Simic, Milana; Prcic, Sonja; Matic, Milan; Gajic, Branislava (Acta medicae Medianae, 2022)
Lentigo maligna melanoma (LMM) is an invasive melanoma most commonly occurring on the head and neck. The diagnosis is aided by specific dermoscopic criteria and confirmed by biopsy. The treatment of LMM is surgical excision. There are alternative therapies for its precursor lesion lentigo maligna (LM, also known as Hutchinson’s melanotic freckle) – melanoma in situ, and they include the application of topical 5% imiquimod cream. Our patient had a 7 x 4 cm lesion with dermoscopic features of both LM and LMM. The diagnosis was confirmed by pathohistological examination of the incisional biopsy. The patient, concerned about the aesthetic outcome, refused surgical treatment and was treated by 5% imiquimod cream. Dermoscopy aided the clinical diagnosis, it allowed for a non-invasive follow-up and tailoring of the treatment in order to attain satisfactory results – evanescence of dermoscopic features suggestive of LM and LMM and an aesthetically acceptable outcome after treatment.